The Giving Conformity on Stimulation for The Development of Children - Eny Qurniyawati (Health Notions, 2017)
Not achieving optimal child development resulted in reduced earnings of as much as 20% as adults that have implications for national development of the nation. The purpose of this study is to describe the relationship of stimulation with the development of children 4-5 years.This research was observation analytic with case control design, was conducted in the Banteng Village Playing Group, Wungu Sub District, Madiun District in May 2017. Case groups were children with dubious developments, while control groups were children with appropriate development. With purposive sampling there were 32 children and their mother. Results showed that factors were influencing the stimulation of mother with high risk age (OR: 51.55; CI95% = 1.37 to 193.93 P = 0.033), mother with low education (OR: 19.88; 95% CI = 1.01 to 390.58 p = 0.049). Mothers with more than 2 children (OR: 24.49; CI95% = 1.37 to 438.04, p = 0.030). Giving stimulation associated with the development of children (OR: 12.50; 95% CI = 2.29 to 68.24, p = 0.002). Did not giving of stimulation has implications on child development is not appropriate. Keywords: Maternal characteristics, Stimulation, Development of toddlers